Ontogenetic changes in functional matrices and facial bone remodeling - Brachetta Aporta, Natalia (2023)
According to the functional matrix hypothesis, changes in size and shape and location of facial bones during individual ontogeny are influenced by periosteal and capsular matrices. However, the interaction of the functional matrices with the distribution of areas of bone remodeling has not yet been extensively studied. Here we evaluate the changes in the volume of the paranasal sinuses and orbital capsule with age, and their association with facial growth arising from bone remodeling patterns of the upper and midfacial region in a sample of prehistoric human populations from South America. We found an association between capsule size and bone cell proportions; however, the trajectories of variation are ambiguous across bones. The frontal and maxillary sinuses had a significant increase from 4.5 up to 14.5 years of age, while the orbital capsule had an increase in volume even in adult stages. In turn, the volume of the frontal sinus increases while the bone formation remains relatively stable in subadults and decreases in adults, while the maxilla and the zygomatic bones display a lower proportion of formation when the bones are growing. Our study contributes information concerning the covariation between bone growth remodeling and the increments of the capsular matrices.